41.8k views
5 votes
X − 3 = −5x+ 3 need the work shown please

User Xeos
by
4.9k points

1 Answer

4 votes

Answer:

x = 1

Explanation:

x - 3 = -5x + 3

+3 +3 Add 3 to both sides to get rid of/move the -3 on the left side

x = -5x + 6

+5x +5x Add 5x to both sides to get rid of/move the -5x on the right side. You want to combine the variables to solve the equation.

6x = 6

x = 6/6

x = 1

User Jigar Thakkar
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.